Tatanan Dunia Multipleks Dan Kebijakan Luar Negeri Prabowo Subianto - Asrudin (Universitas Komputer Indonesia, 2025)
The liberal international order was initially established by European powers in the 19th century and further developed by the United States after World War II, the deadliest conflict in human history. This concept refers to a rules-based system designed to govern international relations and legitimize American hegemony. However, this order began to shake after Donald Trump occupied the White House. Trump withdrew America's full involvement in international affairs, considering them misaligned with national interests. His administration withdrew from several UN organizations, including the Human Rights Council, UNESCO, UNRWA, and WHO. Additionally, he pulled the U.S. out of the Paris Agreement on Climate Change and halted all foreign aid. He initiated a tariff war against multiple countries, which significantly undermined the liberal international order. This shift has given rise to what Amitav Acharya describes as a multiplex world order. This article will explore the multiplex world order and discuss how the Prabowo government should respond through Indonesia's foreign policy. To achieve this research objective, a qualitative research method is employed. This approach allows the author to collect, analyze, and interpret non-numerical data, facilitating a deeper understanding of the core aspects of this article's research. Keywords —Donald Trump, The Liberal international Order, Multiplex World Order, Indonesia's foreign policy, Prabowo.